Effect of in vitro digestion-fermentation on green and roasted coffee bioactivity: The role of the gut microbiota. (1st May 2019) - Pérez-Burillo, Sergio; Mehta, Trupthi; Esteban-Muñoz, Adelaida; Pastoriza, Silvia; Paliy, Oleg; Ángel Rufián-Henares, José
Highlights: The effect of in vitro digestion-fermentation on green and roasted coffee was studied. The fermented fraction was more antioxidant than regular and digested coffees. Individual polyphenols and SCFAs production were different in green coffees. The microbial community was different after fermenting green and roasted coffees. Green and roasted coffees behave as different foods after digestion-fermentation. Abstract: Coffee is one of the most consumed beverages and has been linked to health in different studies. However, green and roasted coffees have different chemical composition and therefore their health properties might differ as well. Here, we study the effect of in vitro digestion-fermentation on the antioxidant capacity, phenolic profile, production of short-chain fatty acids (SCFAs), and gut microbiota community structure of green and roasted coffee brews. Roasted coffees showed higher antioxidant capacity than green coffees, with the highest level achieved in fermented samples. Polyphenol profile was similar between green and roasted coffees in regular coffee brews and the digested fraction, but very different after fermentation. Production of SCFAs was higher after fermentation of green coffee brews. Fermentation of coffee brews by human gut microbiota led to different community structure between green and roasted coffees. All these data suggest that green and roasted coffees behave as different types of food.